Primary malignant melanoma of the female urethra: A case report - Kazuhiro Watanabe; Go Hasegawa; Katsunori Kashima; Yo Sato; Noboru Hara; Tsutomu Nishiyama (Urology Case Reports, 2021)
Primary malignant melanoma of a female urethra is extremely rare. A 71-year-old female was referred to our hospital with bleeding from the urethral meatus. Magnetic resonance imaging revealed a mass of 25 mm in diameter at the external urethral meatus. She underwent anterior pelvic exenteration and ileal conduit diversion. Histopathological findings were urethral malignant melanoma, pT3apN0M0 (stage IIA). Nine months after surgery, computed tomography revealed a local recurrence in the pelvis, the patient was treated with immunotherapy using combined nivolumab and ipilimumab; however, she did not respond to treatment and died 22 months following diagnosis.